Detection, Identification and Titration of Anti- C (RJ I4) Allo-Antibody in a Multi-Transfused HHA Patient Referred to the Department of Transfusion Medicine of BSMMU - Khatun, A; Biswas, J; Habibullah, MM; Shill, N; Salam, A; Alam, MM (TAJ: Journal of Teachers Association, 2009)
It is a Report of a case of transfusion induced alloimmunization of anti-c (Rh-4) in multi transfused HHA.Following top-up transfusion DHTR resu lted in this multi transfused HHA. Patients was referred to the transfusion medicine department of BSMMU to detect the cause/s of DHTR from the Hematology department of Bogra MCH. High titrated (1: 256) anti-c alloantibody were detected, identified in this patient by the standardized sensitive method of immunohematological testing at the department of transfusion medicine, BSMMU. When incompatible RCCs arc transfused the amount of antibody in recipient's serum may be too low to effect red cell destruction or even to be not detected by sensitive compatibility tests. However Transfusion may provoke as anamnestic immune response so that a few days after transfusion a rapid increased in antibody concentration develops and rapid destruction of transfused red cells occur. Hemoglobinuira is not uncommon in DHTRs. and causes HDN During TOP-UP transfusion to each and every HHAs genotypically matched antigen negative RCC to be practiced to avoid DHTR. Unlike AIHA it is possible to identify and detect alloantibody responsible for the DHTR by meticulous immunohematological testing and processing. TAJ 2009; 22(1): 272-275